Early oxidative burst and anthocyanin-mediated antioxidant defense mechanism impart resistance against Sclerotinia sclerotiorum in Indian mustard. (July 2022) - Singh, Manjeet; Avtar, Ram; Lakra, Nita; Pal, Ajay; Singh, Vivek K.; Punia, Rakesh; Kumar, Neeraj; Bishnoi, Mahavir; Kumari, Nisha; Khedwal, Rajbir Singh; Choudhary, Raju Ram
Abstract: The current study builds on our prior findings that anthocyanin buildup around the pathogen inoculation site confers resistance to S. sclerotiorum resistance in Indian mustard. However, the mechanism by which anthocyanin accumulation confers resistance is largely unknown. To better understand this mechanism, we compared the disease responses and biochemical profiling of two contrasting and wild type genotypes of Indian mustard [Sclerotinia stem rot-resistant RH 1222–28 (WR) and susceptible Varuna (WS)], as well as two anthocyanin contrasting mutants [anthocyanin-more (PM) and anthocyanin-devoid (AM) mutant] during different infection phases. Regardless of the inoculation time, disease examination revealed that WR and PM had considerably ( P ≤ 0.05 ) lower mean lesion length (MLL) and rate of lesion expansion than WS and AM. Compared to WS and AM, biochemical results showed that WR and PM responses to infection were earlier, more timely regulated, and more robust. In the resistant WR and PM, hydrogen peroxide (H2 O2 ) and superoxide anions (O2 −1 ) accumulated rapidly and peaked during the early infection stage (2 days after inoculation; DAI), whereas in the susceptible WS and AM, accumulation was stronger and more intense in the later infection stage (8 DAI). Compared to the susceptible genotype (WS), the resistant genotype (WR) had significantly higher anthocyanin accumulation, a lower rate of lipid peroxidation, and a strong, efficient, and timely regulated antioxidant system that limited pathogen colonization and disease development. The anthocyanin-rich mutant (PM) is more resistant to ROS-induced oxidative damage. It has a slower rate of lesion development than the anthocyanin-deficient (AM) mutant, which has lower anthocyanin accumulation and higher oxidative stress with weak antioxidative potential, resulting in significantly ( P ≤ 0.05 ) longer stem lesion length and rate of lesion expansion. These findings imply that during distinct infection phases of S. sclerotiorum, a well-coordinated oxidants/antioxidants system in terms of intensity and timing regulates Sclerotinia stem rot resistance/susceptibility. Overall, anthocyanin accumulation around the pathogen infection site appears to play a critical role in altering the ROS producing and scavenging machinery in Indian mustard, which contributes to resistance to S. sclerotiorum . Highlights: Compared to the susceptible genotype (Varuna), the resistant genotype (RH 1222-28) had significantly higher anthocyanin accumulation, a lower rate of lipid peroxidation, and a strong, efficient, and timely regulated antioxidant system that limited pathogen colonization and disease development. The anthocyanin-more mutant (PM) is more resistant to ROS- induced oxidative damage. It has a slower rate of lesion development than the anthocyanin-deficient (AM) mutant, which has lower anthocyanin accumulation and higher oxidative stress with weak antioxidative potential, resulting in significantly (P ≤ 0.05) longer stem lesion length and rate of lesion expansion. The resistant genotype acclimated better than the susceptible genotype by maintaining cellular redox potential through well-coordinated pro- and anti-oxidant defence, which included higher anthocyanin accumulation, maintenance of the ascorbate–glutathione redox pool, and timely regulation of antioxidant enzymes. The anthocyanins accumulation around the infection site appears to play a critical role in modifying ROS producing and scavenging machinery, contributing to S. sclerotiorum resistance in Indian mustard.